Sedentary time in older men and women: an international consensus statement and research priorities. Issue 21 (19th July 2017) - Dogra, Shilpa; Ashe, Maureen C; Biddle, Stuart J H; Brown, Wendy J; Buman, Matthew P; Chastin, Sebastien; Gardiner, Paul A; Inoue, Shigeru; Jefferis, Barbara J; Oka, Koichiro; Owen, Neville; Sardinha, Luís B; et al.
Abstract : Sedentary time is a modifiable determinant of poor health, and in older adults, reducing sedentary time may be an important first step in adopting and maintaining a more active lifestyle. The primary purpose of this consensus statement is to provide an integrated perspective on current knowledge and expert opinion pertaining to sedentary behaviour in older adults on the topics of measurement, associations with health outcomes, and interventions. A secondary yet equally important purpose is to suggest priorities for future research and knowledge translation based on gaps identified. A five-step Delphi consensus process was used. Experts in the area of sedentary behaviour and older adults (n=15) participated in three surveys, an in-person consensus meeting, and a validation process. The surveys specifically probed measurement, health outcomes, interventions, and research priorities. The meeting was informed by a literature review and conference symposium, and it was used to create statements on each of the areas addressed in this document. Knowledge users (n=3) also participated in the consensus meeting. Statements were then sent to the experts for validation. It was agreed that self-report tools need to be developed for understanding the context in which sedentary time is accumulated. For health outcomes, it was agreed that the focus of sedentary time research in older adults needs to include geriatric-relevant health outcomes, that there is insufficient evidence to quantify the dose–response relationship, that there is a lack of evidence on sedentary time from older adults in assisted facilities, and that evidence on the association between sedentary time and sleep is lacking. For interventions, research is needed to assess the impact that reducing sedentary time, or breaking up prolonged bouts of sedentary time has on geriatric-relevant health outcomes. Research priorities listed for each of these areas should be considered by researchers and funding agencies.